Kampung warna-warni jodipan Evaluasi Penataan Lanskap Riparian Sungai Pada Kawasan Kampung Warna-Warni Jodipan Berbasis Persepsi Dan Preferensi Masyarakat: Penambahan vegetasi - Nathania, Grafia; Alfian, Rizki; Santoso, Dian Kartika; Dwi Julianto, Reza Prakoso (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2024)
Malang Colorful Village or also known as Jodipan Colorful Village (KWJ) is one of the first tourist villages in Malang City. Every corner of this village is decorated with various bright and bright colors that can attract attention. Not only with wall paint, various handicrafts and decorations also enliven the atmosphere of this Colorful Village. Interestingly, this place is always frequented by tourists who want to take photos or just see first hand the beauty of the former slums. Various potential conditions and problems cause problems for the environment and the stability of soil sedimentation around the Brantas river. To anticipate this, it is necessary to evaluate the river riparian landscape arrangement, so that appropriate landscape planning can be made. Interview techniques were used in this research to measure perceptions and preferences for five variables, namely knowledge, utilization, comfort, visuals and policy. Next, it was analyzed using a Likert Scale. The results of community perceptions and preferences aim to produce an integrated and sustainable form of landscape management. The desired achievements are maintaining ecological balance, increasing community welfare, and maintaining the socio-cultural conditions of the community. A management scheme based on a balance between the ecological environment, community welfare and socio-culture can be realized by knowing the perceptions and preferences of the community. At the level of comfort, it can be concluded that people feel more comfortable living close to the river, especially in Jodipan Colorful Village, the river is used as a tourist attraction with a glass bridge over it. The public's perception of the visuals and arrangement of vegetation can be concluded that the community needs additional vegetation by arranging it neatly. The addition of vegetation makes local people feel more comfortable. In general, people use rivers as their source of life. Rivers are considered important and are used as a source of life for local communities. policy can be concluded that the community understands that not all policies are fully implemented by the community.